Anethole inhibits human U87 Glioma cell proliferation by inducing apoptosis via the PI3K/AKT pathway - Ahmed Abdullah Al Awadh; Elhashimi Eltayb Hassan; Omer Mohamed Shoaib; Osman A.E. Elnoubi; Saadalnour Abusail Mustafa; Yasir Mohammed Althayrayan; Majed Ahmed Althayrayan; Mohammed Merae Alshahrani (PLoS ONE, 2025)
Glioma is characterized by rapid progression, resistance to conventional therapies, and poor prognosis. Current treatments are often limited by their inability to selectively target tumor cells. Natural compounds, such as anethole, have shown promising anticancer properties in various cancers, but their efficacy in glioblastoma remains unexplored. This study investigates the anticancer activity of anethole in glioma cells, focusing on its influence on cell proliferation, apoptosis, and the PI3K/Akt pathway. Human glioma cell lines (U87-MG and LN-229) and normal human astrocytes (NHA) were treated with anethole. Cell viability was evaluated using the CCK-8 assay, while colony formation and AO/EB staining assays evaluated proliferation and apoptosis, respectively. Cell viability was evaluated using the CCK-8 assay, while colony formation and AO/EB staining assessed proliferation and apoptosis, respectively. Western blotting was used to analyze apoptosis-related markers and PI3K/AKT pathway proteins. Molecular docking assessed anethole–PI3K binding, and in silico analyses (SwissTargetPrediction, KEGG, RummaGEO) identified putative targets and pathways. Anethole exhibited selective cytotoxicity, with significantly lower IC₅₀ values for U87-MG (10.8 ± 0.42 µM) and LN-229 (12.5 ± 0.51 µM) compared to NHA cells (61.5 ± 1.27 µM), calculated from three independent experiments with triplicate wells. Colony formation was notably inhibited in a dose-dependent manner. AO/EB staining and Western blotting confirmed this with upregulation of Bax, downregulation of Bcl-2, and reduced phosphorylation of PI3K and Akt. Molecular docking revealed strong binding affinity of anethole to PI3K (−9.32 kcal/mol), and Western blot showed inhibition of PI3K and Akt phosphorylation. Anethole selectively inhibits glioma cell proliferation by inducing apoptosis and suppressing the PI3K/Akt cascade. These observations underscore its potential as a novel therapeutic agent for glioblastoma, warranting further preclinical and clinical investigations.